Agrobacterium VirE3 Uses Its Two Tandem Domains at the C-Terminus to Retain Its Companion VirE2 on the Cytoplasmic Side of the Host Plasma Membrane - Li, X. (Frontiers Media S.A., 2021)
10.3389/fpls.2020.00464